A method for preparing high-strength sintered foil for aluminum electrolytic capacitors

By mixing the modified carbon quantum dot powder with aluminum powder and performing a sintering process, the problems of mechanical strength and carbon residue in traditional sintered foils are solved, and sintered foils with high strength, low carbon residue and excellent dielectric properties are achieved.

CN119153237BActive Publication Date: 2025-02-25NANTONG HAIXING ELECTRONICS +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411667905.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

Traditional sintered foils have poor mechanical strength and low specific surface area due to aggregation of aluminum powder, and carbon residue after sintering affects dielectric properties.

Method used

Modified carbon quantum dot powder is used to mix it with aluminum powder, and a high-strength sintered foil is formed through the sintering process to reduce the use of binder to reduce carbon residue.

Benefits of technology

The mechanical strength and specific surface area of ​​the sintered foil are improved, carbon residue is reduced, dielectric performance is improved, and environmental pressure and economic costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153237B_ABST
    Figure CN119153237B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of aluminum electrolytic capacitors, and specifically to a method for preparing a high-strength sintered foil for aluminum electrolytic capacitors. The method for preparing a high-strength sintered foil for aluminum electrolytic capacitors of the present invention comprises the following steps: 1. Evenly mix modified carbon quantum dot powder and aluminum powder, and add a solvent and stir evenly to obtain a modified aluminum powder slurry; 2. Further add a binder and an additive and stir evenly to obtain a mixed slurry; 3. Evenly coat the slurry on the surface of an aluminum foil substrate and solidify it; 3. Sinter the obtained aluminum foil substrate; 4. Chemically form the sintered foil to obtain an anode powder sintered foil. Compared with the prior art, the high-strength sintered foil for aluminum electrolytic capacitors of the present invention avoids carbon residue while ensuring higher capacity and mechanical strength, thereby improving the dielectric properties of the sintered foil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum electrolytic capacitors, and in particular to a method for preparing a high-strength sintered foil for aluminum electrolytic capacitors. Background Art

[0002] The electrode foil for traditional aluminum electrolytic capacitors is made by chemically / electrochemically etching the aluminum foil to create pores to increase the specific surface area. This method consumes a large amount of acid and the waste liquid generated increases the environmental cost. In recent years, a method of obtaining a high specific surface area by sintering aluminum powder on the surface of an aluminum substrate instead of electrochemical etching has emerged.

[0003] Patent technology document CN115064387A discloses a method for preparing anode foil based on sintered aluminum powder, which includes the following steps: 1) putting aluminum powder or aluminum alloy powder slurry into a solvent and dispersing it evenly; 2) adding a binder into the solvent; 3) coating the slurry of step 2) on an aluminum foil substrate; 4) sintering; in the first stage, the temperature is raised to 80-150°C and kept warm for 20 minutes; in the second stage, the temperature is slowly raised to 400-500°C and kept warm for 1-2 hours, and reducing gas is introduced during the insulation stage of the second stage; in the third stage, the temperature is raised to 630-659°C, sintered for 1-5 hours to form a sintered foil, and reducing gas is introduced in the third stage; 5) chemical formation to obtain the anode foil. In the present invention, reducing gas is added to the inert protective gas during sintering, which can ensure that the aluminum powder or aluminum alloy powder will not be oxidized during sintering, thereby ensuring the sintering quality.

[0004] Although powder sintered foil can obtain a larger specific surface area than corroded foil, and the preparation process does not use various corrosive acids, which greatly reduces the environmental load and economic cost. However, the current sintered foil preparation process often leads to poor mechanical strength and low specific surface area due to the aggregation of aluminum powder, and the carbon residue after sintering affects the electrical properties of the sintered foil. Therefore, it is urgent for technicians to solve the above problems. Summary of the invention

[0005] In view of this, the purpose of the present invention is to propose a method for preparing a high-strength sintered foil for aluminum electrolytic capacitors to solve the problems that the traditional sintered foil has poor mechanical strength and low specific surface area due to aluminum powder aggregation, and the carbon residue after sintering affects the dielectric properties of the sintered foil.

[0006] Based on the above purpose, the present invention provides a method for preparing a high-strength sintered foil for an aluminum electrolytic capacitor, characterized in that it comprises the following steps:

[0007] S1: Mixing modified carbon quantum dot powder, aluminum powder, binder, additive and solvent, stirring evenly to obtain a mixed slurry;

[0008] S2: coating the mixed slurry on the surface of aluminum foil and vacuum drying;

[0009] S3: sintering the aluminum foil obtained in step S2 to obtain a sintered foil;

[0010] S4: chemically forming the sintered foil to obtain a high-strength sintered foil for aluminum electrolytic capacitors;

[0011] The preparation steps of the modified carbon quantum dot powder in step S1 are as follows:

[0012] The carbon quantum dots are dispersed in ethanol, and after ultrasonication, the pH is adjusted to 7-9, and then 10-15 ml of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is added, and the mixture is reacted at 40-60° C. for 12-20 hours, and then centrifuged, washed, filtered, and dried to obtain modified carbon quantum dot powder;

[0013] The carbon quantum dots, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and ethanol are used in a ratio of 10 g: 10-15 ml: 150-200 ml;

[0014] The particle size of the carbon quantum dots is 1-10 nm.

[0015] Preferably, the weight ratio of the modified carbon quantum dot powder to the aluminum powder in step S1 is 0.01-0.1:1.

[0016] Preferably, the binder in step S1 is one of epoxy resin, polyvinylidene fluoride, carboxymethyl cellulose and acrylic resin.

[0017] Preferably, the additive in step S1 is one of sodium dodecylbenzene sulfonate, stearic acid and polyvinyl alcohol.

[0018] Preferably, the solvent in step S1 is one of ethanol, ethylene glycol and N-methylpyrrolidone.

[0019] Preferably, the ratio of the aluminum powder to the solvent in step S1 is 1 g:2 ml.

[0020] Preferably, the amount of the binder used is 3%-5% of the mass of the solvent.

[0021] Preferably, the amount of the additive is 1%-5% of the solvent mass.

[0022] Preferably, the purity of the aluminum powder in step S1 is above 99.9%, and the particle size is 10-50 μm.

[0023] Preferably, the mixing method in step S1 is one of ultrasonic mixing, mechanical stirring and grinding.

[0024] Preferably, the coating method in step S2 is one of brushing, rolling and spraying.

[0025] Preferably, the thickness of the aluminum foil in step S2 is 30-80 μm.

[0026] Preferably, the vacuum drying temperature in step S2 is 40-200° C., in order to avoid agglomeration of the powder during solvent evaporation.

[0027] Preferably, the sintering procedure in step S3 is to first keep the temperature at 300-450° C. for 1-10 h, and then keep the temperature at 500-650° C. for 1-5 h in a nitrogen atmosphere.

[0028] Preferably, the specific steps of the formation in step S4 are to boil the sintered foil and then sequentially perform primary formation, secondary formation, tertiary formation, quaternary formation, passivation, post-formation, heat treatment, post-secondary formation, and passivation.

[0029] Preferably, the boiling is to boil the sintered foil in 90-98° C. water for 5-20 min.

[0030] Preferably, the primary chemical process is to place the aluminum foil in a boric acid solution having a mass percentage concentration of 1%-20% and an ammonium pentaborate solution having a mass percentage concentration of 0.2%-5%, and to heat the aluminum foil at 80-98°C and a current density of 0.1 A / cm 2 , the voltage is 200V, and the formation time is 10-20min.

[0031] Preferably, the secondary chemical process is to place the aluminum foil in a boric acid solution having a mass percentage concentration of 1%-10% and an ammonium pentaborate solution having a mass percentage concentration of 0.2%-2%, and to heat the aluminum foil at 80-98°C and a current density of 0.1 A / cm 2 The secondary formation is carried out under the conditions of 430V and 430V, and the formation time is 10-20min.

[0032] Preferably, the three-stage chemical process is to place the aluminum foil in a boric acid solution having a mass percentage concentration of 2%-10% and an ammonium pentaborate solution having a mass percentage concentration of 0.1%-1%, and to heat the aluminum foil at 80-98°C and a current density of 0.1 A / cm 2 The three-stage formation is carried out under the conditions of 590V and 590V, and the formation time is 8-15 min.

[0033] Preferably, the four-stage chemical process is to place the aluminum foil in a boric acid solution having a mass percentage concentration of 4%-10% and an ammonium pentaborate solution having a mass percentage concentration of 0.1%-1%, and to heat the aluminum foil at 80-98°C and a current density of 0.1 A / cm 2 The four-stage formation is carried out under the conditions of 620V and 620V, and the formation time is 15-30 min.

[0034] Preferably, the passivation process is to place the aluminum foil in a phosphoric acid solution with a mass percentage concentration of 3%-6%, the temperature is controlled at 50-80° C., and the immersion time is 5-10 min.

[0035] Preferably, the latter chemical process is to place the aluminum foil in a boric acid solution having a mass percentage concentration of 10%-12% and an ammonium pentaborate solution having a mass percentage concentration of 0.1%-1%, and to conduct the reaction at 80-98°C and a current density of 0.1 A / cm 2 The subsequent formation is carried out under the conditions of 620V and 5-8min.

[0036] Preferably, the heat treatment process is to keep the aluminum foil at 400-550° C. for 2-5 minutes.

[0037] Preferably, the post-chemical process is to place the aluminum foil in a boric acid solution having a mass percentage concentration of 4%-9% and an ammonium pentaborate solution having a mass percentage concentration of 0.1%-1%, and to heat the aluminum foil at 80-95°C and a current density of 0.1 A / cm 2 The post-second formation is carried out under the conditions of 620V and 620V, and the formation time is 5-10 min.

[0038] Preferably, the passivation process is to place the aluminum foil in a diammonium phosphate solution with a mass percentage concentration of 1%-5%, and immerse it at 60-80° C. for 5-8 minutes.

[0039] Beneficial effects of the present invention: Compared with the traditional electrochemical corrosion process, the high-strength sintered foil for aluminum electrolytic capacitors of the present invention does not need to consume a large amount of acid solution, avoids the generation of waste acid, and reduces environmental pressure and economic costs.

[0040] The high-strength sintered foil for aluminum electrolytic capacitors of the present invention is obtained by mixing aluminum powder with modified carbon quantum dots and coating the mixture on the surface of the aluminum foil. Compared with the sintered foil prepared by the traditional process, the specific volume and mechanical strength of the sintered foil are further improved, the peeling area is further reduced, and while maintaining a high specific volume and mechanical strength, the use of binder is reduced, thereby reducing carbon residue and improving the dielectric properties of the sintered foil. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art description.

[0042] Figure 1Schematic diagrams of surface microscopic photographs of the sintered foils obtained in Examples 1, 2, 3 of the present invention and Comparative Example 4, wherein (a) is a schematic diagram of the surface microscopic photograph of the sintered foil obtained in Comparative Example 4, (b) is a schematic diagram of the surface microscopic photograph of the sintered foil obtained in Example 1, (c) is a schematic diagram of the surface microscopic photograph of the sintered foil obtained in Example 2, and (d) is a schematic diagram of the surface microscopic photograph of the sintered foil obtained in Example 3. DETAILED DESCRIPTION

[0043] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0044] Example 1: A high-strength sintered foil for aluminum electrolytic capacitors, the specific preparation steps are as follows:

[0045] (1) Disperse 10 g of carbon quantum dots with a particle size of 1 nm in 150 ml of ethanol, homogenize by ultrasonication, adjust the pH to 7, then add 10 ml of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, react at 40 °C for 12 h, centrifuge, wash, filter, and dry to obtain modified carbon quantum dots;

[0046] (2) Disperse 100 g of aluminum powder and 1 g of modified carbon quantum dot powder in 200 ml of ethanol, and after ultrasonic homogenization, add 4.8 g of epoxy resin and 1.6 g of sodium dodecylbenzene sulfonate, and stir evenly to obtain a mixed slurry;

[0047] (3) The mixed slurry is evenly coated on the surface of an aluminum foil substrate with a thickness of 50 μm by brushing, and dried under vacuum at 40° C.

[0048] (4) In a nitrogen atmosphere, the aluminum foil obtained in step (3) is first kept at 300° C. for 1 h and then kept at 500° C. for 1 h to obtain a sintered foil;

[0049] (5) The sintered foil was boiled in 90°C water for 5 min, and then placed in a 1% by mass concentration of boric acid and 0.2% by mass concentration of ammonium pentaborate at 80°C and a current density of 0.1 A / cm 2 The first stage was formed under the conditions of 200 V voltage and 10 min formation time. After being taken out and washed with water, it was placed in a 1% by mass concentration of boric acid and a 0.2% by mass concentration of ammonium pentaborate solution at 80 ° C and a current density of 0.1 A / cm 2 The secondary formation was carried out under the conditions of 430V and 10min; after being taken out and washed with water, it was placed in a 2% by mass concentration of boric acid and a 0.1% by mass concentration of ammonium pentaborate solution at 80℃ and a current density of 0.1 A / cm 2The three-stage formation was carried out under the conditions of 590V and 8min; after being taken out and washed with water, it was placed in a 4% by mass concentration of boric acid and a 0.1% by mass concentration of ammonium pentaborate solution at 80℃ and a current density of 0.1 A / cm 2 , 620V, and the four-stage formation was carried out under the conditions of 15 min; after being taken out and washed with water, it was placed in a phosphoric acid solution with a mass percentage concentration of 3%, the temperature was controlled at 50°C, and the immersion time was 5 min; after being taken out and washed with water, it was placed in a boric acid solution with a mass percentage concentration of 10% and an ammonium pentaborate solution with a mass percentage concentration of 0.1%, and the current density was 0.1 A / cm 2 The second formation was carried out under the conditions of 620V and 5min; after being taken out and washed with water, it was placed in an oven at 400℃ for 2min; then it was placed in a 4% by mass concentration of boric acid and 0.1% by mass concentration of ammonium pentaborate solution at 80℃ and a current density of 0.1 A / cm 2 After being taken out and washed with water, it was placed in a 1% by mass concentration of ammonium dihydrogen phosphate solution, immersed at 60°C for 5 minutes, washed with water, and dried to obtain a high-strength sintered foil for aluminum electrolytic capacitors.

[0050] Example 2: A high-strength sintered foil for aluminum electrolytic capacitors, the specific preparation steps are as follows:

[0051] (1) Disperse 10 g of carbon quantum dots with a particle size of 5 nm in 180 ml of ethanol, homogenize by ultrasonication, adjust the pH to 8, then add 13 ml of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, react at 50 °C for 16 h, centrifuge, wash, filter, and dry to obtain modified carbon quantum dots;

[0052] (2) Disperse 100 g of aluminum powder and 5 g of modified carbon quantum dot powder in 200 ml of ethanol, and after ultrasonic homogenization, add 6.4 g of epoxy resin and 4.8 g of sodium dodecylbenzene sulfonate, and stir evenly to obtain a mixed slurry;

[0053] (3) The mixed slurry is evenly coated on the surface of an aluminum foil substrate with a thickness of 50 μm by brushing, and dried under vacuum at 100° C.;

[0054] (4) In a nitrogen atmosphere, the aluminum foil obtained in step (3) was first kept at 400° C. for 5 h and then kept at 600° C. for 3 h to obtain a sintered foil;

[0055] (5) The sintered foil was boiled in 94°C water for 13 min and then placed in a 10% by mass concentration of boric acid and 3% by mass concentration of ammonium pentaborate at 90°C and a current density of 0.1 A / cm 2 The first stage was formed under the conditions of 200 V voltage and 15 min of formation time. After being taken out and washed with water, it was placed in a 5% by mass concentration of boric acid and a 1% by mass concentration of ammonium pentaborate solution at 88 ° C and a current density of 0.1 A / cm 2 The secondary formation was carried out under the conditions of 430V and 15min; after being taken out and washed with water, it was placed in a 6% by mass concentration of boric acid and a 0.5% by mass concentration of ammonium pentaborate solution at 88℃ and a current density of 0.1 A / cm 2 The three-stage formation was carried out under the conditions of 590V and 12 min; after being taken out and washed with water, it was placed in a boric acid solution with a mass percentage concentration of 7% and an ammonium pentaborate solution with a mass percentage concentration of 0.5%, and the current density was 0.1 A / cm 2 , 620V, and the formation time is 20 min; after taking it out and washing it with water, it is placed in a phosphoric acid solution with a mass percentage concentration of 5%, the temperature is controlled at 70°C, and the immersion time is 8 min; after taking it out and washing it with water, it is placed in a boric acid solution with a mass percentage concentration of 11% and an ammonium pentaborate solution with a mass percentage concentration of 0.5%, and the current density is 0.1 A / cm 2 The second formation was carried out under the conditions of 620V and 600V for 6min; after being taken out and washed with water, it was placed in an oven at 450℃ for 3min; then it was placed in a 7% by mass concentration of boric acid and 0.5% by mass concentration of ammonium pentaborate solution at 88℃ and a current density of 0.1 A / cm 2 The post-second formation was carried out under the conditions of 620V and 800V, and the formation time was 8 min; after taking it out and washing it with water, it was placed in a 3% by mass concentration of ammonium dihydrogen phosphate solution, immersed at 70°C for 7min, washed with water, and dried to obtain a high-strength sintered foil for aluminum electrolytic capacitors.

[0056] Example 3: A high-strength sintered foil for aluminum electrolytic capacitors, the specific preparation steps are as follows:

[0057] (1) Disperse 10 g of carbon quantum dots with a particle size of 10 nm in 200 ml of ethanol, homogenize by ultrasonication, adjust the pH to 9, then add 15 ml of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, react at 60 ° C for 20 h, centrifuge, wash, filter, and dry to obtain modified carbon quantum dots;

[0058] (2) Disperse 100 g of aluminum powder and 10 g of modified carbon quantum dot powder in 200 ml of ethanol, and after ultrasonic homogenization, add 8 g of epoxy resin and 8 g of sodium dodecylbenzene sulfonate, and stir evenly to obtain a mixed slurry;

[0059] (3) The mixed slurry is evenly coated on the surface of an aluminum foil substrate with a thickness of 50 μm by a brushing method, and dried at 200° C. in a vacuum environment;

[0060] (4) Under a nitrogen atmosphere, the aluminum foil obtained in step (3) was first kept at 450° C. for 10 h and then kept at 650° C. for 5 h to obtain a sintered foil;

[0061] (5) The sintered foil was boiled in 98°C water for 20 min and then placed in a 20% by mass concentration of boric acid and 5% by mass concentration of ammonium pentaborate at 98°C and a current density of 0.1 A / cm 2 The first stage was formed under the conditions of 200 V voltage and 20 min; after being taken out and washed with water, it was placed in a 10% by mass concentration of boric acid and a 2% by mass concentration of ammonium pentaborate solution at 98 ° C and a current density of 0.1 A / cm 2 The secondary formation was carried out under the conditions of 430V and 430V for 20min. After being taken out and washed with water, it was placed in a 10% by mass concentration of boric acid and a 1% by mass concentration of ammonium pentaborate solution at 98℃ and a current density of 0.1 A / cm 2 The three-stage formation was carried out under the conditions of 590V and 15 min; after being taken out and washed with water, it was placed in a 10% by mass concentration of boric acid and a 1% by mass concentration of ammonium pentaborate solution at 98°C and a current density of 0.1 A / cm 2 , 620V, and the four-stage formation was carried out under the conditions of 30 min; after being taken out and washed with water, it was placed in a phosphoric acid solution with a mass percentage concentration of 6%, the temperature was controlled at 80°C, and the immersion time was 10 min; after being taken out and washed with water, it was placed in a boric acid solution with a mass percentage concentration of 12% and an ammonium pentaborate solution with a mass percentage concentration of 1%, and the current density was 0.1 A / cm 2 The second formation was carried out under the conditions of 620V and 8min; after being taken out and washed with water, it was placed in an oven at 550℃ for 5min; then it was placed in a 9% by mass concentration of boric acid and 1% by mass concentration of ammonium pentaborate solution at 95℃ and a current density of 0.1 A / cm 2The post-second formation was carried out under the conditions of 620V and 620V, and the formation time was 10 min; after taking it out and washing it with water, it was placed in a 5% by mass concentration of ammonium dihydrogen phosphate solution, immersed at 80°C for 8min, washed with water, and dried to obtain a high-strength sintered foil for aluminum electrolytic capacitors.

[0062] Comparative Example 1: A sintered foil for an aluminum electrolytic capacitor, which differs from Example 2 in that the carbon quantum dots are not modified, and the specific preparation steps are as follows:

[0063] (1) Disperse 100 g of aluminum powder and 5 g of carbon quantum dot powder with a particle size of 5 nm in 200 ml of ethanol, and after ultrasonic homogenization, add 6.4 g of epoxy resin and 4.8 g of sodium dodecylbenzene sulfonate, and stir to obtain a mixed slurry;

[0064] (2) The mixed slurry is evenly coated on the surface of an aluminum foil substrate with a thickness of 50 μm by brushing, and dried at 100° C. in a vacuum environment;

[0065] (3) In a nitrogen atmosphere, the aluminum foil obtained in step (2) was first kept at 400°C for 5 h and then kept at 600°C for 3 h to obtain a sintered foil;

[0066] The remaining steps are the same as in Example 2.

[0067] Comparative Example 2: A sintered foil for an aluminum electrolytic capacitor, which differs from Example 2 in that the carbon quantum dots with a particle size of 5 nm are replaced with an equal amount of carbon powder with a particle size of 20 μm, and the specific steps are as follows:

[0068] (1) Disperse 10 g of carbon powder with a particle size of 20 μm in 180 ml of ethanol, homogenize by ultrasonication, adjust the pH to 8, then add 13 ml of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, react at 50 °C for 16 h, centrifuge, wash, filter, and dry to obtain modified carbon powder;

[0069] (2) Disperse 100 g aluminum powder and 5 g modified carbon powder in 200 ml ethanol, mix them evenly with ultrasound, add 6.4 g epoxy resin and 4.8 g sodium dodecylbenzene sulfonate, stir evenly to obtain a mixed slurry;

[0070] (3) The mixed slurry is evenly coated on the surface of an aluminum foil substrate with a thickness of 50 μm by brushing, and dried under vacuum at 100° C.;

[0071] (4) In a nitrogen atmosphere, the aluminum foil obtained in step (3) was first kept at 400° C. for 5 h and then kept at 600° C. for 3 h to obtain a sintered foil;

[0072] The remaining steps are the same as in Example 2.

[0073] Comparative Example 3: A sintered foil for an aluminum electrolytic capacitor, which differs from Example 2 in that no carbon quantum dots are added, and the specific preparation steps are as follows:

[0074] (1) Disperse 100 g of aluminum powder in 200 ml of ethanol, and after ultrasonic homogenization, add 6.4 g of epoxy resin and 4.8 g of sodium dodecylbenzene sulfonate, and stir to obtain a mixed slurry;

[0075] (2) The mixed slurry is evenly coated on the surface of an aluminum foil substrate with a thickness of 50 μm by brushing, and dried at 100° C. in a vacuum environment;

[0076] (3) In a nitrogen atmosphere, the aluminum foil obtained in step (2) was first kept at 400°C for 5 h and then kept at 600°C for 3 h to obtain a sintered foil;

[0077] The remaining steps are the same as in Example 2.

[0078] Comparative Example 4: A sintered foil for aluminum electrolytic capacitors, which differs from Example 2 in that no carbon quantum dots are added, and the amount of binder used is 10% of the mass of the solvent. The specific preparation steps are as follows:

[0079] (1) Disperse 100 g of aluminum powder in 200 ml of ethanol, and after ultrasonication, add 16 g of epoxy resin and 4.8 g of sodium dodecylbenzene sulfonate, and stir to obtain a mixed slurry;

[0080] (2) The mixed slurry is evenly coated on the surface of an aluminum foil substrate with a thickness of 50 μm by brushing, and dried at 100° C. in a vacuum environment;

[0081] (3) In a nitrogen atmosphere, the aluminum foil obtained in step (2) was first kept at 400°C for 5 h and then kept at 600°C for 3 h to obtain a sintered foil;

[0082] The remaining steps are the same as in Example 2.

[0083] Performance Testing

[0084] Specific capacitance: The test is carried out using the method in the industry standard SJ / T 11140-2022 "Electrode foil for aluminum electrolytic capacitors".

[0085] Bending test: The test is carried out using the method in the industry standard SJ / T 11140-2022 "Electrode foil for aluminum electrolytic capacitors".

[0086] Tensile strength: tested using the method in the industry standard SJ / T 11140-2022 "Electrode foil for aluminum electrolytic capacitors".

[0087] Peeling area: The peeling area is tested using the method in ISO 2409-1992 "Cross-cut test for paints and varnishes". The test results are shown in Table 1.

[0088] Table 1 Performance test results

[0089]

[0090] Table 2 Surface element content test results

[0091]

[0092] It can be seen from Example 2 and Comparative Example 1 in Table 1 that the mechanical properties and specific volume of the sintered foil are further improved by modifying the carbon quantum dots in the present invention. This may be because the hydrogen bonding effect between the modified carbon quantum dots and the binder is further enhanced compared to the unmodified carbon quantum dots, which can improve the bonding force between the aluminum powder particles, thereby further improving the mechanical properties of the sintered foil and further reducing the peeling area.

[0093] It can be seen from Example 2 and Comparative Example 2 in Table 1 that the present invention improves the mechanical properties and specific volume of the sintered foil by adopting carbon quantum dots with a particle size of 1-10 nm. This may be because compared with micron-sized carbon powder, it has a larger specific surface area and is more tightly combined with the aluminum powder to reduce agglomeration and voids, thereby further improving the mechanical properties and specific volume of the sintered foil.

[0094] It can be seen from Example 2 and Comparative Examples 1 and 2 in Table 1 that the present invention mixes aluminum powder and modified carbon quantum dots. On the one hand, nanoscale carbon quantum dots are attached to the surface of aluminum powder by electrostatic adsorption, and at the same time, the Coulomb repulsion between the carbon quantum dots avoids the agglomeration of aluminum powder in the slurry, thereby obtaining a uniformly dispersed aluminum powder slurry, which improves the specific volume of the sintered foil; on the other hand, relative to the unmodified carbon quantum dots, the hydrogen bonding effect between the modified carbon quantum dots and the binder is further enhanced, thereby improving the bonding force between the aluminum powder particles, thereby further improving the mechanical properties of the sintered foil and further reducing the peeling area.

[0095] It can be seen from Example 2 in Table 1 and Comparative Examples 3 and 4 as well as Table 2 that, compared with the conventional method for preparing sintered foil, the present invention reduces the use of binder, reduces the carbon content, avoids carbon residue, and thereby improves the dielectric properties of the sintered foil while ensuring that the specific volume and mechanical properties remain unchanged.

[0096] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A method for preparing a high-strength sintered foil for an aluminum electrolytic capacitor, characterized in that: The following steps are involved: S1: Mixing modified carbon quantum dot powder, aluminum powder, binder, additive and solvent, stirring evenly to obtain a mixed slurry; S2: coating the mixed slurry on the surface of aluminum foil and vacuum drying; S3: sintering the aluminum foil obtained in step S2 to obtain a sintered foil; S4: chemically forming the sintered foil to obtain a high-strength sintered foil for aluminum electrolytic capacitors; The preparation steps of the modified carbon quantum dot powder in step S1 are as follows: The carbon quantum dots are dispersed in ethanol, and after ultrasonication, the pH is adjusted to 7-9, and then 10-15 ml of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is added, and the mixture is reacted at 40-60° C. for 12-20 hours, and then centrifuged, washed, filtered, and dried to obtain modified carbon quantum dot powder; The carbon quantum dots, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and ethanol are used in a ratio of 10 g: 10-15 ml: 150-200 ml; The particle size of the carbon quantum dots is 1-10 nm.

2. The method for preparing a high-strength sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The weight ratio of the modified carbon quantum dot powder to the aluminum powder in step S1 is 0.01-0.1:

1.

3. The method for preparing a high-strength sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The binder in step S1 is one of epoxy resin, polyvinylidene fluoride, carboxymethyl cellulose and acrylic resin.

4. The method for preparing a high-strength sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The additive in step S1 is one of sodium dodecylbenzene sulfonate, stearic acid and polyvinyl alcohol.

5. The method for preparing a high-strength sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The solvent in step S1 is one of ethanol, ethylene glycol and N-methylpyrrolidone.

6. The method for preparing a high-strength sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: In step S1, the ratio of aluminum powder to solvent is 1g:2ml; the amount of binder is 3%-5% of the mass of the solvent, and the amount of additive is 1%-5% of the mass of the solvent.

7. The method for preparing a high-strength sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The coating method in step S2 is one of brushing, rolling and spraying.

8. The method for preparing a high-strength sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The sintering procedure in step S3 is to first keep the temperature at 300-450° C. for 1-10 h, and then keep the temperature at 500-650° C. for 1-5 h in a nitrogen atmosphere.

9. The method for preparing a high-strength sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The specific steps of the formation in step S4 are to boil the sintered foil and then sequentially perform primary formation, secondary formation, tertiary formation, quaternary formation, passivation, post-formation, heat treatment, post-secondary formation, and passivation.

Citation Information

Patent Citations

  • Preparation method of anode foil based on sintered aluminum powder

    CN115064387A

  • Traceable additive and preparation method thereof

    CN111423596A

  • Preparation method of high-dielectric composite powder sintered foil

    CN115172061A